SISTEM PENDIDIKAN PESANTREN TRADISIONAL DALAM ERA MODERN - Syamsul A'dlom (LP3M IAI Al-Qolam Malang, 2015)
Pondok Pesantren now needs to be read as well as a heritage of the intellectual culture of the archipelago. Moreover, in a number of specific aspects, pesantren should also be understood as a bastion of culture itself because of the historical role it has played. This expectation, of course, is not too far from the cultural construction that was outlined by the founders. Imagined as a center for the development of science and culture with religious dimension or local improvisation, pesantren is also prepared by its founders as a motor for the transformation of the community and the nation. Interestingly, all the wishful thinking is actually departed from the â€œairport of traditionsâ€ of local communities. In the course of history, the prominent and influential role of pesantren played up to now is the concentrating and pioneering work in maintaining and preserving the teachings of Sunni Islam (Ahl al-Sunnah wa al-Jamaâ€™ah) and developing religious studies through the treasury of traditional book (al-Kutub al-Qadimah), which is often referred to, by the schools themselves, a â€œdeepening of religionâ€ (tafaqquh fi al-Din), as a result of the creative dialectic among the tradition of deep studies, educational system, and the interaction patterns of Kyai-Santri-communities. The development has spawned a modern era of progress. Fundamental changes in the structure of culture is often hit at various establishment. As a result, there is a necessity to hold contextualization buildings culture with the dynamics of modernization, including the pesantren education system. Therefore, the pesantren education system should make efforts to stay relevant, constructive and viable. Keywords: Education System, Traditional Pesantren, Modernization Era.